The Similarities Between al-Ghazālī’s Science of the Hereafter and Rasāil Ikhwān al-Safā - Abdullah Özkan (İslam Tetkikleri Dergisi)
In Munqidh, al-Ghazālī states that there were four classes of seekers of truth: theologians, followers of the doctrine of Ta‘līm, philosophers, and Sufis. He depicts himself here as a Sufi who denounces the others, especially the philosophers. This image of al-Ghazālī became the major perception of him from the beginning. This perception changed in the twentieth century. The most recent scholarship views him as a scholar who was heavily influenced by philosophy and disseminated its teachings in disguise. However, the focus is given mostly to the philosophy of Avicenna while searching the source of this influence. While not denying the influence of Ibn Sīnā, this study argues that Rasā’il Ikhwān Ṣafā’ must be taken seriously as a major source of philosophical influence on al-Ghazālī’s thought despite the negative remarks he makes about them. For its purpose, this study considers al-Ghazālī as a philosopher whose main concern was to direct the attention of his readers to their inner states and the behaviors resulting from them. This concern led him to search for and develop an ethical theology in which the theory of the soul and its purification played a role of utmost importance. For this purpose, al-Ghazālī presented a new science in Iḥyā. This study tries to show that al-Ghazālī found the essential ingredients of this theology in Rasā’il, gave it a new form with a new name, “the Science of the Hereafter” with its two subdivisions: the science of practice and the science of unveiling.